The Holy Land in the Middle Ages six travelers' accounts - Binyamin ben Yonah mi-Ṭudelah -1173; Hieronymus, Sophronius Eusebius 345-420; Paula Heilige 347-404; Eustochium Sancta 368-419; Muqaddasī, Muḥammad Ibn-Aḥmad al- 946-990; Nāṣir Ḫusrau 1004-1078; Theodoricus Monachus ca. 12. Jh (Italica Press historical travel series, 2017)
"Presents texts by medieval Christian, Muslim and Jewish travelers, including: St. Jerome, Paula & Eustochium, Mukaddasi of Jerusalem, Nâsir-i-Khusrau, Theoderich of Würzburg and Benjamin of Tudela. Includes photos, plans, maps, views, bibliography"...Provided by publisher